2016
DOI: 10.1038/ni.3327
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance is established in polyclonal CD4+ T cells by distinct mechanisms, according to self-peptide expression patterns

Abstract: Studies of mouse monoclonal CD4+ T cell repertoires have revealed several mechanisms of self-tolerance, however, which mechanisms operate in normal repertoires is unclear. Here, polyclonal CD4+ T cells specific for green fluorescent protein expressed in different organs were studied, allowing determination of the effects of specific expression patterns on the same epitope-specific T cells. Peptides presented uniformly by thymic antigen-presenting cells were tolerated by clonal deletion, whereas thymus-excluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
186
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(212 citation statements)
references
References 62 publications
8
186
0
3
Order By: Relevance
“…ZnT8 186–194 -reactive CD8 + T cells from T1D patients also expressed higher levels of aurora A kinase, which might hint at increased mitotic activity in the T1D setting. Mirroring this observation, an anergic phenotype has been reported for self-reactive CD8 + T cells in non-autoimmune subjects (22, 36), which may be at least partially imprinted in the thymus (33, 37). …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…ZnT8 186–194 -reactive CD8 + T cells from T1D patients also expressed higher levels of aurora A kinase, which might hint at increased mitotic activity in the T1D setting. Mirroring this observation, an anergic phenotype has been reported for self-reactive CD8 + T cells in non-autoimmune subjects (22, 36), which may be at least partially imprinted in the thymus (33, 37). …”
Section: Discussionmentioning
confidence: 87%
“…In this scenario, tolerance to β-cell Ags may depend primarily on T-cell ignorance (32, 37). Three observations are noteworthy in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…For these other specificities, resistance to avidity maturation may be epigenetically imprinted, similar to T cell-intrinsic hyporesponsiveness, which makes cells resistant to secondary encounter of antigen (Philip et al, 2017; Schietinger et al, 2012), or may be constrained by regulatory cells distinct from classical Tregs. Studies of T cells in tumor microenvironments that are deemed dysfunctional and of self-specific T cells (Black et al, 2014; Kuball et al, 2009; Malhotra et al, 2016; Moon et al, 2011; Soong et al, 2014; Souders et al, 2007; Wong et al, 2008; Yu et al, 2015) have also revealed that many of these cells are low avidity at the population level, supporting the idea that tolerance, whether spontaneously acquired in the tumor microenvironment or upon self-antigen encounter or, as we show in this study, therapeutically induced by costimulation blockade therapy, may be simultaneously enforced through multiple mechanisms, one of which being the preservation of low-avidity repertoire for the relevant antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that Treg frequencies may be lower or functionally altered in humans with T1D and NOD mice (33, 34). Additionally, higher affinity interactions with self-peptide/MHC and TCR have been shown to be required for the expression and maintenance of Foxp3 (35-37). In order to address the impact of thymic antigen dose and pMHC stability on the selection of insulin specific T cells, we utilized TCR retrogenic technology (38-40) to generate mice that co-express either low or high affinity insulin reactive TCRs (on T cells) and either insulin or insulin mimetope R22E (on antigen presenting cells (APCs)).…”
Section: Introductionmentioning
confidence: 99%